2018
DOI: 10.1097/hs9.0000000000000055
|View full text |Cite
|
Sign up to set email alerts
|

Increased Red Cell KCNN4 Activity in Sporadic Hereditary Xerocytosis Associated With Enhanced Single Channel Pressure Sensitivity of PIEZO1 Mutant V598M

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
(25 reference statements)
0
11
1
Order By: Relevance
“…Although HEK293 cells constitute a powerful expression system extensively used to study stretch-activated channels (and channels in general), these above considerations together with the results presented here question the relevance of using HEK293 cells to study the gating of mechano-sensitive channel from RBC. Of note, in a previous study, the pressure sensitivity of V598M PIEZO1 mutant expressed in HEK293 cells was shown to slightly increase compared to WT (Gnanasambandam et al, 2018). This discrepancy with our present results would suggest an even more complex regulation of PIEZO1 activity depending on the different experimental conditions among diverse laboratories, such as (i) different cellular clones, (ii) stages of cellular cycle, (iii) cellular senescence, and (iv) number of replicates.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although HEK293 cells constitute a powerful expression system extensively used to study stretch-activated channels (and channels in general), these above considerations together with the results presented here question the relevance of using HEK293 cells to study the gating of mechano-sensitive channel from RBC. Of note, in a previous study, the pressure sensitivity of V598M PIEZO1 mutant expressed in HEK293 cells was shown to slightly increase compared to WT (Gnanasambandam et al, 2018). This discrepancy with our present results would suggest an even more complex regulation of PIEZO1 activity depending on the different experimental conditions among diverse laboratories, such as (i) different cellular clones, (ii) stages of cellular cycle, (iii) cellular senescence, and (iv) number of replicates.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, these PIEZO1 mutants are likely to induce a constitutive Na + , K + , and Ca 2+ leak in RBC. Moreover, in previously published patch-clamp experiments on RBC carrying the V598M PIEZO1 mutant (in whole cell and cellattached configurations), a constitutive cation leak, increased conductance and increased spontaneous activity were observed (Rapetti-Mauss et al, 2017;Gnanasambandam et al, 2018). To characterize mutant PIEZO1 features, they were expressed in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The V598M mutation has also previously been reported in an unrelated HX case with a typical phenotype associating hemolysis, iron overload, and neonatal ascites, with functional studies revealing a lower PIEZO1 activation threshold and increased K + influx sensitive to Gardos channel inhibition. 53 These data suggest that mutations involving amino-acid 598 may be associated with a higher risk of PE development.…”
Section: Piezo1-hx and Perinatal Edemamentioning
confidence: 89%
“…Thus, in DHS1, RBC dehydration is largely due to inappropriate activation of the Gardos channel (see Section 2 above) and can be reverted in vitro using the selective Gardos inhibitor Senicapoc (Figure 2(B)). 31,53 Senicapoc may thus represent an attractive treatment option for symptomatic HX, especially as the molecule has been shown to be safe in clinical trials for the treatment of sickle‐cell disease, although its efficacy on dehydration and hemolysis parameters was not shown to reduce the frequency of vaso‐occlusive crises 54,55 . Strikingly, Gardos channelopathies and DHS1 are not entirely comparable, differing in the severity of hematological phenotype, occurrence of perinatal edema, thrombotic risk after splenectomy, and perhaps iron overload risk 28,50,56 .…”
Section: Erythroid Cell Defects In Piezo1‐hxmentioning
confidence: 99%
“…Mutated KCNN4 Channels have alterations of kinetic of open‐closure of the channel similar to PIEZO1 mutants (Rapetti‐Mauss et al , ; Rivera et al , ). Recent studies demonstrate that chronic KCNN4‐driven red cell dehydration and intracellular cation imbalance (also caused by PIEZO1 mutations) can lead to functional inactivation of KCNN4 activity in DHS RBCs (Gnanasambandam et al , ; Rivera et al , ).…”
Section: Red Blood Cell Membrane Disorders: Classification and Pathogmentioning
confidence: 99%